Pengawasan Teknologi Finansial Melalui Regulatory Sandbox oleh Bank Indonesia Atau Otoritas Jasa Keuangan Berdasarkan Perspektif Keadilan Bermartabat - Rizky P.P Karo Karo; Laurenzia Luna (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2019)
Financial technology (TF) cannot be released by the community both in rural areas or urban areas. TF provides a paradigm shift for the community. TF makes it easy for humans to make financial transactions simply by using a smart phone (HP) that humans can make payment transactions, borrow money. People will certainly choose TF that is safe and reliable and profitable, but sometimes people rarely know that a good and correct TF is a TF that has passed the Regulatory Sandbox (RS) test or a limited trial room. Two Government institutions that are authorized to carry out hospitals are Bank Indonesia (BI) through Bank Indonesia Regulation No: 19/12 / PBI / 2017 concerning Financial Services and Financial Services Authority (OJK) Implementation through “Financial Services Authority Regulation NUMBER 13 /POJK.02/2018 about Digital Financial Innovation in the Financial Services Sector”. The formulation of the problem raised is how is the TF supervision mechanism through the hospital implemented by BI or OJK? The method used in this scientific paper is a normative juridical method, using secondary data in the form of primary legal material consisting of laws and regulations relating to TF, secondary legal material in the form of scientific articles, journals and tertiary legal materials in the form of dictionaries. The research results obtained are that TF must pass the trial in the Regulatory Sandbox applied by BI or OJK. BI and OJK have the authority to determine whether the proposed TF is feasible or not feasible. RS is a significant method, according to the laws and regulations to get a TF that is suitable and safe for consumers and contains dignified justice, justice for business people and consumers.